2020
DOI: 10.1111/jfpp.15025
|View full text |Cite
|
Sign up to set email alerts
|

Development of high protein extruded snack using composite flour and milk proteins through response surface methodology

Abstract: With the benefits of protein and relative retention of nutrition over other fried snacks, this study was used to formulate crunchy snacks using composites of rennet casein (RC), barley flour (BF), sweet potato flour (SPF), and rice flour (RF) with emphasis on protein. Central Composite Rotatable Design (CCRD) of Response Surface Methodology (RSM) was utilized to study the combined effects of SPF (20–35), BF (15–30), RF (30–40), and RC (10–30); all being in parts; on Water Absorption and Solubility Indices, L*,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The use of temperatures close to or lower than those of the control may also not have been high enough to break the amylase walls and increase the solubility (Jakkanwar et al, 2018). This result is similar to that of Yadav et al (2021), who also observed a reduction in the solubility value with higher replacement rates.…”
Section: Resultssupporting
confidence: 89%
“…The use of temperatures close to or lower than those of the control may also not have been high enough to break the amylase walls and increase the solubility (Jakkanwar et al, 2018). This result is similar to that of Yadav et al (2021), who also observed a reduction in the solubility value with higher replacement rates.…”
Section: Resultssupporting
confidence: 89%